Quality of Life of Patients on Maintenance Hemodialysis in Relation to Hemoglobin Level: A Multicenter Study from a Developing Country (BIRDEM Medical Journal, 2017)
Background: Anemia is common in patients with end stage renal disease (ESRD) and is associated with impaired quality of life (QOL). This study was done to evaluate the QOL of ESRD patients on maintenance hemodialysis (MHD) with different levels of hemoglobin (Hb).Methods: This cross-sectional study was conducted from January to December 2013 on 135 adult ESRD patients on MHD for ?4 months, at hemodialysis units of three tertiary care hospitals in Dhaka, Bangladesh. The patients were divided into three groups based on Hb levels (Group 1: Hb 11 gm/dl, n=37, 28%), provided their Hb levels were stable [ie. maintained with erythropoietin (EPO) or blood transfusion (BT) or both] over the previous four months. Subjects were interviewed by principal investigator using Kidney Disease Quality of Life Short Form Tool (KDQOL-SF-36 version 1.3) consisting of two domains with 38 questions with each item put on a 0 to 100 range, higher scores indicating better QOL.Results: The mean age was 50+12 years with male predominance (male:female = 1.5:1). Mean duration of hemodialysis was 12±11.8 months (range 9 to 66 months). The average QOL score was 50. Comparison of QOL parameters between the three groups showed that symptoms/problems, effects of kidney disease, burden of kidney disease, cognitive function, quality of social interaction and sleep in the kidney disease specific domain as well as pain, emotional well-being, social function and energy/fatigue scale scores in the general health related domain were significantly higher in the group 2 and group 3 than group 1 patients (each with p